Characteristics and Genesis of Laterite Bauxite in Sompak District and Surrounding Areas, Landak Regency, West Kalimantan - Tri Winarno; Rinal K. Ali; Harrys Simangunsong; Almiftahurrizqi Almiftahurrizqi (Indonesian Journal on Geoscience, 2023)
West Kalimantan has very large bauxite resources, reaching 2.07 billion tons, equivalent to 57.32% of the total bauxite resources in Indonesia with bauxite reserves of 0.84 billion tons or equivalent to 66.77% of the total national mineral reserves. The researched area covers Sompak District and surrounding areas, Landak Regency, West Kalimantan. This research aims to determine geological conditions, laterization, and characteristics of laterite bauxite in the studied area. Methods used in this research are geological mapping, lateritic mapping, and petrographic and geochemical analyses. The lithology of the researched area is composed of granodiorite, porphyry quartz diorite, granite, porphyry andesite, porphyry basalt, alluvial, and swamp deposits. Laterite profiles in the researched area generally consist of topsoil, latosol, bauxite, and clay zone. The laterite bauxite derived from granodiorite is classified as a medium grade, laterite bauxite from porphyry quartz diorite is classified as high-grade bauxite, laterite bauxite from andesite porphyry is classified as low-medium grade bauxite, and laterite bauxite from porphyry basalt in the studied area is classified as high grade bauxite. Laterite bauxites in the researched area were formed from weathered parent rocks which were intermediate - alkaline igneous rock.